Distribution of major and trace elements in surface sediments of the western Gulf of Thailand: Implications to modern sedimentation. (1st April 2016) - Liu, Shengfa; Shi, Xuefa; Yang, Gang; Khokiattiwong, Somkiat; Kornkanitnan, Narumol
Abstract: In this study, we analyze major and trace elements (SiO2, Al2 O3, Fe2 O3, CaO, K2 O, MgO, Na2 O, TiO2, P2 O5, MnO, Cu, Pb, Ba, Sr, V, Zn, Co, Ni, Cr, and Zr) and grain size of 157 surface sediment samples from the western Gulf of Thailand (GoT). On the basis of the space distribution characteristics, the study area can be classified into three geochemical provinces. Province I covers the northern and northwestern coastal zones of the GoT, including the whole upper GoT and thus the sediments from the rivers in the area. It contains high contents of SiO2 . Province II is located in the middle of the GoT and has similar geochemistry composition as the South China Sea (SCS). It contains sediments that are characterized by higher contents of Na2 O, TiO2, Ba, Cr, V, Zn, Zr, and Ni. Province Ш is located in the lower GoT, close to Malaysia. Major and trace elements in this area showed complex distribution patterns, which may be due to terrestrial materials from Malay rivers combining with some sediments from the SCS in this province. The results also indicate that grain size is the controlling factor in elemental contents, and that the hydrodynamic environment and mineral composition of the sediments play an important role in the distribution of these elements. The anthropogenic impact of heavy metal introduction (especially Cr, Zn, Cu, and Pb) can be seen in surface sediments from the nearshore region of Chantaburi province and north of Samui Island. Highlights: The GoT can be classified into three provinces based on element compositions. Terrestrial materials are the main provenience of modern sediment. Hydrodynamic environment plays important roles during the sediment transportion.